2014
DOI: 10.1080/07370008.2014.918132
|View full text |Cite
|
Sign up to set email alerts
|

Like Teacher, Like Student? Conceptions of Children From Traditional and Constructive Teachers Regarding the Teaching and Learning of String Instruments

Abstract: More and more studies are dealing with the association between teachers' and students' conceptions of learning and teaching and their actual practices in the classroom. Nevertheless, few studies have directly researched the influence of teachers' conceptions on those held by their students. Our primary objective was to analyze the influence of music teachers' conceptions on the ideas held by their students regarding learning and teaching. We interviewed 60 children: 30 with teachers who held traditional concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
3
37
0
6
Order By: Relevance
“…Their high scores suggest that they perceived learning by web-searching as the conceptions of increasing knowledge, the application of information, and the acquisition of understanding and of new information. Previous studies concerning students" conceptions of learning in general had shown that students had more constructivist learning conceptions in more conventional learning environments (Leung, Wong & Wong, 2013;López-Íñiguez & Pozo, 2014). Although the focus of this study was pre-school educators" conceptions of learning by web-searching, the analysis results revealed similar findings to those of past studies about students" conceptions of learning in a different context.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Their high scores suggest that they perceived learning by web-searching as the conceptions of increasing knowledge, the application of information, and the acquisition of understanding and of new information. Previous studies concerning students" conceptions of learning in general had shown that students had more constructivist learning conceptions in more conventional learning environments (Leung, Wong & Wong, 2013;López-Íñiguez & Pozo, 2014). Although the focus of this study was pre-school educators" conceptions of learning by web-searching, the analysis results revealed similar findings to those of past studies about students" conceptions of learning in a different context.…”
Section: Resultssupporting
confidence: 75%
“…However, the research focus on preschool teachers is still limited. Therefore, it is hypothesized in this study that preschool educators" conceptions of learning would show a relationship with the context of the learning, as suggested by Leung, Wong and Wong (2013) and López-Íñiguez and Pozo (2014). That is to say, conceptions of learning are considered to be contextually dependent, and therefore some variation is expected to be found between State of the literature  Some studies suggest that early year educators' positive views of web-based technology are essential for influencing teaching practices, while the educators themselves can play an important role in supporting and extending children's experiences with web-based technology.…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, research in instrumental music instruction has shown that the beliefs and practices of constructivist teachers who focus on students' prior knowledge and motivations can have a positive impact on students' learning strategies, teaching and learning beliefs, studying autonomy, and sense of engagement in the classroom (López-Íñiguez & Pozo, 2014a;2014b;, all factors related to the quality of teaching and learning music. These results resonate with Johansen (2007), who emphasises the significance of systematically conducted research as a bottom-up activity -based on data collected from teachers' and students' experiences of teaching and learning processes within their specific subjectswhen establishing quality systems in higher music education.…”
Section: Quality Of Teaching and Learning In Higher Music Educationmentioning
confidence: 99%
“…This method has been effective for analyzing open oral responses (Bécue, Lebart, & Rajadell, 1992) and inferring conceptions of the process of acquisition and knowledge transfer in both children and adults in specific fields of learning (Baccalá & de la Cruz, 2000;Scheuer et al, 2002;Scheuer, de la Cruz, Pozo, Echenique, & Márquez, 2009) and recently in the field of learning and teaching music (López-Íñiguez & Pozo, 2014b;Marín et al, 2013). The lexicometrical procedure enables us to determine the most representative answers from participants according to statistical criteria and provides more inductive access to the participant's actual discourse than would certain types of content analysis in which the categories are set by the researchers' theoretical framework, leading to circular reasoning.…”
Section: Instrument and Proceduresmentioning
confidence: 99%
“…Nevertheless, it enables more in-depth analysis than would have been possible by simple observation (López-Íñiguez & Pozo, 2014b). For each question, we apply a two-step analysis, which we shall describe in detail, because lexicometry has not often been used in research into cultural psychology (for an in-depth description, see Bécue-Bertaut, 2008); & Lebart & Salem, 1998).…”
Section: Instrument and Proceduresmentioning
confidence: 99%